Dari Idealisme ke Pragmatisme: Pergeseran Paradigma dalam Pengembangan Hukum Ekonomi Syariah di Indonesia - Addiarrahman Addiarrahman; Illy Yanti (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2020)
This study seeks to understand the pragmatism of the development of sharia economic law, and its implications for Islamic financial products in Indonesia. The data comes from the results of interviews and focus group discussions with key informants from academics, practitioners, authorities, and the public. This research finds that pragmatism in the development of Islamic economic law is an approach that still dominates the DSN-MUI fatwas. The pragmatism style used is complex-eclectic pragmatism which is represented through makhÄrij al-fiqhiyyah, which is to choose a mild opinion by sticking to the strongest method or also called